River Tourism - Prideaux, Bruce (CABI, 2014)
Rivers are fascinating places, exhibiting both natural charm and usefulness for a vast array of human activities. Throughout history, rivers have been used as transport routes, as food sources and in more recent times as places to visit and play. Surprisingly, there has been scant recognition of the role of rivers in the tourism industry, a gap which this book was written to fill. In planning this book, Malcolm and I envisaged an end result that would examine the role of rivers as a tourism resource and that would also identify significant issues and trends that later authors may wish to pursue. We hope that this objective has been realized, even if only in part. When discussing how the book would be structured, we were mindful of the need for a text that not only examined a range of river tourism-related issues, many of which are quite diverse, but also one that went beyond the often shallow background discussions of significant natural resources in the context of tourism to provide the reader with a deeper knowledge of aspects of the underlying science of rivers. To this end, the first chapter spends some time examining the hydrological cycle and basic river biology. We strongly believe that for tourism planners, administrators, scholars and students it is difficult to develop informed views on issues such as suitable planning strategies, sustainability and carrying capacity in the absence of at least a basic understanding of these more science-related elements. We hope that we have been able to achieve this objective along with providing relevant and timely information on existing river tourism.